O caso Herculine e o conceito de anormal em Foucault - Silva, Priscila Da [UNIFESP] (2020)
Michel Foucault states that investment in the bodies of individual is a corollary of the relational perspective of power that manifests itself mainly in the normalization of the social, that is, in the set of procedures, mechanisms, practices and discourses that combine, on the one hand, technologies and disciplinary strategies such as separation, classification and surveillance of the set of bodies and, on the other hand, subjectivation techniques that constitute the scope of the individual’s intimacy that, when deciphered, reveals his/her truth. Thus, in the convergence of the training of bodies and the constitution of a mysterious interiority, the modern subject is produced under the sieve of the norm, being conceived as normal what presents in its body and in its subjectivity what is valued, required and authorized, while the abnormal is the one who carries the stigma of deviation, transgression, strangeness, exoticism and what is considered repulsive. Once body, sex and truth are related to form the cohesive and unequivocal individuality that opposes everything that can disturb the coherence of what is conceived as normal, this work will discuss the political problematization of the concept of the abnormal based on the Herculine Barbin case. Our objective is to show how this case constitutes a Foucauldian's paradigm of the formation of the domain of abnormality by mobilizing categories present in different moments of the formation of the abnormal, as well as presenting in its content and in the way the multiple character of the body that can be understood as a strategy to dismantle the power of normalization. Furthermore, the case of the 19th century hermaphrodite allows us to work with texts that belong to different moments in the Foucauldian philosophical journey, thus indicating a possibility of re-reading it from the thematic shift through works that, although composing different phases, enrich their political inquiry.